СМИ Казахстана в условиях глобализации - Donaj, Łukasz; Żumanowicz Nurbekov, Saken (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
The authors present a brief history of independent Kazakhstan and the development of the means of mass information there. At the beginning of December 2010, the Organization for Security and Co-operation in Europe summit took place in Astana. Kazakhstan had chaired the OSCE for a year, enjoying an opportunity to present itself as an ambitious and active player on the international arena. Despite the lack of measurable results, both the Astana summit and the chairing of the organization, which required considerable organizational efforts, turned out to be a test which the entire state apparatus successfully passed and a significant stimulus for its development. That Kazakhstan has been successful also with respect to the development of the media, at least as far as possible, can be proven by the organization of the 9th Media Forum in April 2010, which attracted approximately 450 representatives from around the globe. The Kazakh government pays particular attention to the development of the information infrastructure, which provides a guarantee that the country will participate in the global information space as a full member.